A Review on Current Scenario of Goat Population and Production in Rajasthan, India - Ahari , Poonam; Waiz , Hina Ashraf (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present assessment focuses on the goat industry in Rajasthan, with an emphasis on population and productivity. In India, the goat industry produces 1.21 million tons of goat meat (13.8%), 0.18 million tons of skins, and 6.26 million tons of milk (3%). Goats make up 50% of the total livestock population in Rajasthan and are the dominant species. As of 2019, there were 20.84 million goats in Rajasthan, which represents a 3.81% decrease from the previous census in 2012. Rajasthan produced a total of 3.10 million tons of goat milk and 95.23 thousand tons of goat meat in 2022-2023. The purpose of this review is to shed light on the current goat situation in Rajasthan and encourage entrepreneurship to establish more goat farms to improve the economic status of goat farmers in the region.